Potential of Language and Artistic Art - Nazora Jurayevna, Bekova (International Journal of Psychosocial Rehabilitation, 2020)
Most of the poems of great poet appeared under the Islamic religious scholars. If every ghazal is compared with authentic book, we can see that most poems of Navai are educational and artistic comment of authentic book. At the end, Alisher Navai in his poems used not only open talmeh but also frequently he addressed to hidden form of this artistic art. Divine expression styles as talmeh, iktibos, tafsir are actively used in ghazals of AlisherNavai. The article deals with the masterly use of iktibas, the unacknowledged borrowing in AlisherNavai`s Turkish and Persian ghazals.